MCPggaac haplotype is associated with poor graft survival in kidney transplant recipients with de novo thrombotic microangiopathy - Petr, Vojtech; Csuka, Dorottya; Hruba, Petra; Szilágyi, Ágnes; Kollar, Marek; Slavcev, Antonij; Prohászka, Zoltán; Viklicky, Ondrej (Frontiers in Immunology, 2022)
De novo thrombotic microangiopathy (TMA) is associated with poor kidney graft survival, and as we previously described, it is a recipient driven process with suspected genetic background. Direct Sanger sequencing was performed in 90 KTR with de novo TMA and 90 corresponding donors on selected regions in CFH, CD46, C3, and CFB genes that involve variations with a functional effect or confer a risk for aHUS. Additionally, 37 recipients of paired kidneys who did not develop TMA were analyzed for the MCPggaac haplotype. Three-years death-censored graft survival was assessed using Kaplan-Meier and Cox regression models. The distribution of haplotypes in all groups was in the Hardy-Weinberg equilibrium and there was no clustering of haplotypes in any group. In the TMA group, we found that MCPggaac haplotype carriers were at a significantly higher risk of graft loss compared to individuals with the wild-type genotype. Worse 3-year death-censored graft survival was associated with longer cold ischemia time (HR 1.20, 95% CI 1.06, 1.36) and recipients’ MCPggaac haplotype (HR 3.83, 95% CI 1.42, 10.4) in the multivariable Cox regression model. There was no association between donor haplotypes and kidney graft survival. Similarly, there was no effect of the MCPggaac haplotype on 3-year graft survival in recipients of paired kidneys without de novo TMA. Kidney transplant recipients carrying the MCPggaac haplotype with de novo TMA are at an increased risk of premature graft loss. These patients might benefit from therapeutic strategies based on complement inhibition.